2015
DOI: 10.1021/acs.jcim.5b00043
|View full text |Cite
|
Sign up to set email alerts
|

Test and Evaluation of ff99IDPs Force Field for Intrinsically Disordered Proteins

Abstract: Over 40% eukaryotic proteomic sequences have been predicted as intrinsically disordered proteins (IDPs) or intrinsically disordered regions (IDRs) and confirmed to be associated with many diseases. However, widely used force fields could not well reproduce the conformers of IDPs. A previously ff99IDPs force field was released with CMAP energy corrections for the 8 disorder promoting residues to simulate IDPs. In order to further confirm the performance of ff99IDPs, three representative IDPs systems (arginine-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
85
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 61 publications
1
85
0
Order By: Relevance
“…A variety of simulation methods (MD, Monte Carlo, metadynamics, replica exchange) and different levels of representation (coarse-grained, implicit solvent, all-atom with explicit water) have been used to obtain IDP ensembles. 7,[21][22][23][24][25][26][27][28][29] There are two main challenges encountered in de novo simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of simulation methods (MD, Monte Carlo, metadynamics, replica exchange) and different levels of representation (coarse-grained, implicit solvent, all-atom with explicit water) have been used to obtain IDP ensembles. 7,[21][22][23][24][25][26][27][28][29] There are two main challenges encountered in de novo simulations.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25]27,28,42,[44][45][46] On the other hand, the accuracy of unfolded state and IDP structural ensembles obtained using several widely-used force fields has been called into question. [25][26][27]43,[46][47][48][49][50][51][52][53] Piana et al suggested that modern force fields, including Amber ff99sb*-ildn and CHARMM 22* in particular, produce IDP and unfolded state ensembles that are on average too compact. 48 It has also been suggested that Amber force fields systematically underestimate chain dimensions of IDPs and unfolded states.…”
Section: Introductionmentioning
confidence: 99%
“…19 In order to better reproduce the disordered conformation, a set of AMBER force fields ff99IDPs 20, 21 and others 22 were used, which were developed specially for IDPs with grid-based energy correction maps (CMAP) term 23, 24 to correct the dihedral of backbone for eight disordered-promotion residues of Alanine, Arginine, Glycine, Glutamine, Serine, Glutamic acid, Lysine, and Proline. By adding CMAP energy term, the Φ/Ψ distributions of the eight disorder-promoting residues have been improved with respect to the benchmark data of IDPs, while the root mean squared percentage deviation is less than 0.15% between the benchmark and the simulation 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The Amber 12 package37 and the ff99IDPs force field383940 were used to perform MD simulations. Initial coordinates of wide type was corresponding to S185A/STM complex crystal structure using PyMOL.…”
Section: Methodsmentioning
confidence: 99%